The geochemistry of geothermal fluids of Ölkelduháls and Hveragerði geothermal areas, SW Iceland - Yerko Figueroa Penarrieta 1991- (2021)
The surface geothermal water and steam vent chemistry of the Hveragerði and Ölkelduháls geothermal areas SW Iceland were studied. In total 43 samples were collected of cold springs and rivers, hot springs, and steam vent discharges and their chemical composition analyzed. The chemical composition of geothermal waters at surface was characterized by mildly acid to alkaline pH of 6.06-8.69 and low Cl concentration of 3.32-7.34 ppm and with SiO2 and CO2 generally being the most important dissolved elements with concentration of 38.5-217 and 6.43-486 ppm, respectively. Surface geothermal fluids are considered to be sourced from three end-member waters and mixture of: (1) boiled reservoir liquid, (2) condensed steam and (3) non-thermal water. Relationship between Cl, CO2, SO4 and temperature show evident signatures that surface geothermal fluids in the area are dominantly steam-heated waters with variable mixing ratios between condensed steam and non-thermal waters. No boiled reservoir liquids were observed at surface, these considered to represent boiled liquid fraction of reservoir geothermal fluids. The chemical composition of steam vents was dominated by water (>99 mol%) followed by CO2 (499-6,587 µmol/mol), H2S (17.9-260.4 µmol/mol) and H2 (10.2-194.2 µmol/mol). The composition of steam vents produced upon depressurization boiling of geothermal reservoir fluids differ within the region with steam vent gases being enriched in CO2 and H2S at Ölkelduháls relative to the Hveragerði region, those differences may be related to different heat source for both regions, Hrómundartindur volcanic systems on Ölkelduháls and Grændalur extinct volcanic system in Hveragerði. Gas geothermometry of steam vents estimate temperatures between 230-280°C in Hveragerði and 280-300°C in Ölkelduháls. The surface manifestations were influenced by seismic events, the 2008 earthquake could either open and close fractures or faults rupture and affect the appearance of geothermal manifestations, especially alkaline hot springs reported on ...